PENGARUH PROFITABILITAS, LEVERAGE, VOLUME PERDAGANGAN SAHAM TERHADAP VOLATILITAS HARGA SAHAM - Septian Dwi Permana Putra; Tumirin Tumirin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to determine and analyze the effect of profitability, leverage, stock trading volume on stock price volatility. This research approach is based on a quantitative approach. The population and research sample are companies listed in the LQ45 index for three years from 2020 to 2023. The data analysis technique uses multiple linear regression analysis. The results of the calculation of the hypothesis partially and simultaneously profitability, and stock trading volume have no significant effect on stock price volatility.